"My Words Matter": The Role of Adolescents in Changing Pro-environmental Habits in the Family. Issue 10 (December 2021) - Žukauskienė, Rita; Truskauskaitė-Kunevičienė, Inga; Gabė, Vaida; Kaniušonytė, Goda
A substantial body of research provides evidence for the role of parents in transferring pro-environmental attitudes, values, and behaviors to their children. However, little research has focused on children's active attempts to influence parents' pro-environmental behavior. In a survey involving 508 Lithuanian families, we examined the bidirectional influences of parents' and adolescents' information-induced proenvironmental intentions and behavior. Three plastic waste-related consumption behaviors were studied: purchasing bottled water, using reusable shopping bags, and recycling non-refundable plastic. Results show that both adolescents and their parents influence each other's proenvironmental intentions and behaviors, suggesting that not only parents but also adolescents, may be important agents of positive changes in families and society.